I am invited to a party! - Willems, Mo. (New York : Hyperion Books for Children, an imprint of Disney Book Group, 2007)
Gerald the elephant, who "knows parties," gives his best friend, Piggie, advice for getting ready after Piggie receives her very first party invitation.
0.7
K-3.
K-3
Keywords: Elephants -- Juvenile fiction; Parties -- Juvenile fiction; Swine -- Juvenile fiction; Elephants -- Fiction; Parties -- Fiction; Pigs -- Fiction; Elephants -- Fiction; Parties -- Fiction; Pigs -- Fiction; Humorous fiction; Readers (Publications)